Unmasking differential effects of rosiglitazone and pioglitazone in the combination treatment with n-3 fatty acids in mice fed a high-fat diet - Kus, Vladimir; Flachs, Pavel; Kuda, Ondrej; Bardova, Kristina; Janovska, Petra; Svobodova, Michaela; Jilkova, Zuzana Macek; Rossmeisl, Martin; Wang-Sattler, Rui; Yu, Zhonghao; Illig, Thomas; Kopecky, Jan (PloS one, 2011)
Combining pharmacological treatments and life style interventions is necessary for effective therapy of major diseases associated with obesity, which are clustered in the metabolic syndrome. Acting via multiple mechanisms, combination treatments may reduce dose requirements and, therefore, lower the risk of adverse side effects, which are usually associated with long-term pharmacological interventions. Our previous study in mice fed high-fat diet indicated additivity in preservation of insulin sensitivity and in amelioration of major metabolic syndrome phenotypes by the combination treatment using n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) and rosiglitazone, i.e. an anti-diabetic drug of the thiazolidinedione (TZD) family. We investigated here whether pioglitazone, a TZD-drug in clinical use, could elicit the additive beneficial effects when combined with n-3 LC-PUFA. Adult male mice (C57BL/6N) were fed an obesogenic corn oil-based high-fat diet (cHF) for 8 weeks, or randomly assigned to various dietary treatments (i) cHF+F, cHF with n-3 LC-PUFA concentrate replacing 15% of dietary lipids; (ii) cHF+ROSI, cHF with 10 mg rosiglitazone/kg diet; (iii) cHF+F+ROSI; (iv) cHF+PIO, cHF with 50 mg pioglitazone/kg diet; and (v) cHF+F+PIO, or chow-fed. Plasma concentrations of 163 metabolites were evaluated using a targeted metabolomics approach. Both TZDs preserved glucose homeostasis and normal plasma lipid levels while inducing adiponectin, with pioglitazone showing better effectiveness. The beneficial effects of TZDs were further augmented by the combination treatments. cHF+F+ROSI but not cHF+F+PIO counteracted development of obesity, in correlation with inducibility of fatty acid β-oxidation, as revealed by the metabolomic analysis. By contrast, only cHF+F+PIO eliminated hepatic steatosis and this treatment also reversed insulin resistance in dietary obese mice. Our results reveal differential effects of rosiglitazone and pioglitazone, unmasked in the combination treatment with n-3 LC-PUFA, and support the notion that n-3 LC-PUFA could be used as add-on treatment to TZDs in order to improve diabetic patient's therapy.
Keywords: homeostáza; Male; Obesity; Metabolomics; Fatty Acids, Omega-3; metabolomika; krevní glukóza; Homeostasis; obezita; thiazolidindiony; omega-3 mastné kyseliny; Rosiglitazone; mužské pohlaví; Dietary Fats; Pioglitazone; rosiglitazon; dietní tuky; lipidy; Thiazolidinediones; hypoglykemika; Animals; pioglitazon; zvířata; myši inbrední C57BL; myši; Hypoglycemic Agents; Mice, Inbred C57BL; Lipids; Mice; Blood Glucose